Liver, NAFLD and COVID-19 - Hoffmann, Carlotta; Gerber, Philipp A.; Cavelti-Weder, Claudia; Licht, Louisa; Kotb, Reham; Al Dweik, Rania; Cherfane, Michele; Bornstein, Stefan R.; Perakakis, Nikolaos (Hormone and Metabolic Research, 2022)
Coronavirus disease 2019 (COVID-19) is characterized by a wide clinical spectrum that includes abnormalities in liver function indicative of liver damage. Conversely, people with liver diseases are at higher risk of severe COVID-19. In the current review, we summarize first the epidemiologic evidence describing the bidirectional relationship between COVID-19 and liver function/liver diseases. Additionally, we present the most frequent histologic findings as well as the most important direct and indirect mechanisms supporting a COVID-19 mediated liver injury. Furthermore, we focus on the most frequent liver disease in the general population, non-alcoholic or metabolic-associated fatty liver disease (NAFLD/MAFLD), and describe how COVID-19 may affect NAFLD/MAFLD development and progression and conversely how NAFLD/MAFLD may further aggravate a COVID-19 infection. Finally, we present the long-term consequences of the pandemic on the development and management of NAFLD.
Keywords: NAFLD; COVID-19; MAFLD; SARS-CoV-2; liver